2012
DOI: 10.1021/nn205070h
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Primary Breast Cancers and Metastases in a Transgenic Mouse Model Using Rationally Designed Multifunctional SPIONs

Abstract: Breast cancer remains one of the most prevalent and lethal malignancies in women. The inability to diagnose small volume metastases early has limited effective treatment of stage 4 breast cancer. Here we report the rational development and use of a multifunctional superparamagnetic iron oxide nanoparticle (SPION) for targeting metastatic breast cancer in a transgenic mouse model and imaging with magnetic resonance (MR). SPIONs coated with a copolymer of chitosan and polyethylene glycol (PEG) were labeled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
112
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(112 citation statements)
references
References 41 publications
0
112
0
Order By: Relevance
“…Actively targeted nanoparticles composed of both SPIONs and fluorescent probes have been found to be successful in detecting tumor cells in metastatic breast cancer models (Yang et al, 2009;Kievit et al, 2012;Peirist et al, 2012;). Nanochain of iron oxide nanospheres tagged with cyclic RGD peptide (cRGDfC) and NIR fluorophore formulated by Peiris et al, were found to co-localize efficiently in the tumor endothelium and metastatic lesions in lung and liver (secondary sites) by targeting α v β 3 integrin, which was confirmed using MRI and fluorescence imaging (Peirist et al, 2012).…”
Section: Multi Modal Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Actively targeted nanoparticles composed of both SPIONs and fluorescent probes have been found to be successful in detecting tumor cells in metastatic breast cancer models (Yang et al, 2009;Kievit et al, 2012;Peirist et al, 2012;). Nanochain of iron oxide nanospheres tagged with cyclic RGD peptide (cRGDfC) and NIR fluorophore formulated by Peiris et al, were found to co-localize efficiently in the tumor endothelium and metastatic lesions in lung and liver (secondary sites) by targeting α v β 3 integrin, which was confirmed using MRI and fluorescence imaging (Peirist et al, 2012).…”
Section: Multi Modal Imagingmentioning
confidence: 99%
“…Nanochain of iron oxide nanospheres tagged with cyclic RGD peptide (cRGDfC) and NIR fluorophore formulated by Peiris et al, were found to co-localize efficiently in the tumor endothelium and metastatic lesions in lung and liver (secondary sites) by targeting α v β 3 integrin, which was confirmed using MRI and fluorescence imaging (Peirist et al, 2012). SPION (MRI) coated with chitosan-g-PEG copolymer tagged with Alexa Fluor 647 (Optical imaging) was found to be efficient in detecting spontaneous metastasis and facilitated in vivo MRI analysis and ex vivo fluorescence analysis in the detection of primary as well as micrometastatic lesions (Kievit et al, 2012).…”
Section: Multi Modal Imagingmentioning
confidence: 99%
“…Active targeting of tumor-specific surface receptors that are expressed or overexpressed uniquely on primary tumors was described previously using nanosized medicines (nanomedicines) for the treatment of primary tumors [4][5][6][7][8] and can also be applied for the treatment of metastases [9,10]. However, the genetic mutations that cancer cells undergo increase their resistance to chemotherapeutic agents [11] and, although nanomedicines can overcome some of the mechanisms responsible for this resistance [12], biological barriers such as the high interstitial pressure and the dense extracellular matrix within tumors [13] render their penetration into the tissue largely inefficient beyond the perivascular region [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a wide range of carriers harnessed with targeting ligands or stimuli-responsive moieties that are responsive to external stimuli such as lights, ultrasounds, and magnetic fields have been developed for targeted delivery of biotherapeutics [10, 11]. Among these carriers, superparamagnetic iron oxide nanoparticle (SPION)-based delivery systems have drawn considerable attention because of their unique features such as biocompatibility and superparamagnetism that makes them detectable by MRI for monitoring treatment response and enables magnet-driven drug delivery and release [12-17]. …”
Section: Introductionmentioning
confidence: 99%